2016
DOI: 10.3109/00952990.2015.1125493
|View full text |Cite|
|
Sign up to set email alerts
|

Pilot trial of gabapentin for the treatment of benzodiazepine abuse or dependence in methadone maintenance patients

Abstract: Background Benzodiazepine (BZD) use disorders are a common clinical problem among methadone maintenance treatment patients and have adverse effects on clinical outcomes. Objectives To evaluate gabapentin for the outpatient treatment of BZD abuse or dependence in methadone maintenance patients. Methods Participants (n=19) using BZDs at least 4 days per week were enrolled into an eight-week randomized double-blind placebo-controlled outpatient pilot trial. All participants received a manual-guided supportive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
1
10
0
6
Order By: Relevance
“…Participants ( n = 19) were enrolled in either a placebo arm or a gabapentin arm. 44 The study concluded that no difference was noted in patients on gabapentin compared with placebo. Despite gabapentin being able to increase GABA concentrations, no benefit was found in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Participants ( n = 19) were enrolled in either a placebo arm or a gabapentin arm. 44 The study concluded that no difference was noted in patients on gabapentin compared with placebo. Despite gabapentin being able to increase GABA concentrations, no benefit was found in this study.…”
Section: Resultsmentioning
confidence: 99%
“…1). In total, forty-nine controlled clinical trials were selected and included in this meta-analysis after two suitable one (29,30) were removed because we could not extract enough data, in conformity to the measures of treatment effect that we opted to perform statistical analysis. The trials involved 2724 assigned participants (allocated or completers):1384 participants in the active medication group and 1340 in the placebo group, another group or a control group(non-placebo) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Für Suchterkrankungen insgesamt liegen zahlreiche Therapiestudien vor [39], [44], [45], [46], für Benzodiazepine und BZD-Abhängigkeit allerdings relativ wenige.…”
Section: Psychoedukationunclassified
“…Andere Alternativen sind Non-Benzodiazepin-Anxiolytika, Pregabalin, Gabapentin und Betablocker [40], [44]. Gabapentin hat zwar selber ein gewisses Suchtpotenzial, scheint aber eine gewisse Wirkung beim Benzodiazepinentzug zu habenjedenfalls wäre bei Patienten mit Angstsymptomatik an eine solche Behandlung zu denken.…”
Section: Merkeunclassified